2020
DOI: 10.1017/s1368980020004735
|View full text |Cite
|
Sign up to set email alerts
|

Shifts towards overweight and double burden of malnutrition among socio-economically vulnerable children: a longitudinal ecological analysis of Brazilian municipalities

Abstract: Objective: to investigate the shifts and factors associated with different scenarios resulting from the prevalence of child stunting and overweight in Brazilian municipalities. Design: This is an ecological study using municipality-level panel data of stunting and overweight prevalence and socioeconomic characteristics from 2008 to 2014. The municipalities were classified according to the WHO-UNICEF prevalence thresholds for stunting and overweight, and were categorized into four nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
(49 reference statements)
2
8
0
3
Order By: Relevance
“…While the prevalence of DBM was found to be stable over the studied period, it reached just over 5 % in children aged 2 years or younger. Although this phenomenon has been well-documented in households and communities throughout the stages of life (37) , very little is known with respect to individuals, especially young children. The underlying basis of DBM is not yet fully understood, but some studies have suggested it is particularly related to inadequate nutrition during the period following conception, resulting in restricted intrauterine growth-which might entail delayed linear growth-and subsequent exposure to 'obesogenic environments' (38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…While the prevalence of DBM was found to be stable over the studied period, it reached just over 5 % in children aged 2 years or younger. Although this phenomenon has been well-documented in households and communities throughout the stages of life (37) , very little is known with respect to individuals, especially young children. The underlying basis of DBM is not yet fully understood, but some studies have suggested it is particularly related to inadequate nutrition during the period following conception, resulting in restricted intrauterine growth-which might entail delayed linear growth-and subsequent exposure to 'obesogenic environments' (38,39) .…”
Section: Discussionmentioning
confidence: 99%
“…This study used the IQDAG [14], developed in Brazil, a upper-middle-income country with similar public health issues regarding maternal and child health as South Africa [11][12][13]. Overall, one in ve participants in the current study had poor dietary quality, while only 2.4% achieved a "good quality" diet.…”
Section: Discussionmentioning
confidence: 95%
“…The nine-component Diet Quality Index Adapted for Pregnant Women (IQDAG) was developed in 2018 in Brazil. Like South Africa, Brazil is an upper LMIC experiencing nutrition transition, a triple burden of malnutrition, and a high prevalence of adverse maternal and birth outcomes [11][12][13]. The IQDAG comprises three food groups: legumes, vegetables and fresh fruit; ve nutrients and components vital to pregnancy: iron, folate, calcium, bre and omega-3 (alpha-linolenic acid); and ultra-processed foods as a moderator component [14].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, within our model we could determine the joint effect of stunting in children when having an overweight mother, but also the effect of only child stunting. Literature regarding this topic is scarce, especially in Latin America, where most of the manuscripts are focused on cross-sectional analyses reporting changes in the DBM over time 17,[24][25][26] . A cross-sectional study in Peru evaluated data from children under-5 years of age and their mothers, using information from the Demographic Health Surveys from 1996 to 2016, and reported that during this period there was an important increase in the proportion of children with and without undernutrition that have an overweight or obese mother 17 .…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%